Analysis of the Concept of Work Productivity in Islamic Economic Perspective - Ifna, Nur; Nuringsih, Nuringsih; Jamaluddin, Jamaluddin (Bulletin of Community Engagement, 2023)
One important element of the economy that received great attention from various economic systems, including the Islamic economic system, was the world of work. Work is the main driver of economic activity both micro and macro which is a means for every human being to be able to survive. The purpose of writing is (1) knowing the concept of work or productivity in Islam, (2) knowing the purpose of working in Islamic economics, and (3) knowing work ethics in Islamic economics. The method used in writing this journal is based on qualitative writing using the Literature Review approach. The results and conclusions obtained by work are a way to meet human needs both physical, psychological, and social needs. In addition, work is an activity that has the social support and individual itself. Humans are required to try, not waiting because God does not lower property, science and technology and power from heaven but humans must try themselves. Humans must realize how important economic independence is for every Muslim. Independence or uninvesting for the mercy of others contains risks, that Muslims are required to work hard. And the condition is to understand the basic concepts that work is worship. With this understanding, a high work ethic will be built Keywords: Islamic Economy, Work Productivity, Islamic Economic